Sexo masculino como factor de riesgo para las complicaciones del Covid-19: Male sex as a risk factor for Covid-19 complications - Angulo-Nizama, Manuel Rances (2022)
In different parts of the world, analyses were made on covid-19 positive cases, reaching the conclusion that the percentage of infected men is higher than that of infected women. Cases from 9 years of age to 90 years of age or older were taken into account. Cases studied by covid were taken into account people suffering from other diseases.   ACE2 is the angiotensin-converting enzyme 2, which also acts as a receptor for SARS-CoV 2. This enzyme has a positive correlation with estrogen, this hormone increases the release of acids allowing resistance to this virus. Estrogen was also found to help promote the release of immunoglobulin G and immunoglobulin M. Estrogen also helps release nitric oxide which will help suppress virus replication and acts as a vasodilator, which decreases cardiovascular risk. On the other hand, androgens inhibit the release of immunoglobulin G and immunoglobulin M. This male hormone also has the ability to positively regulate the transcription of transmembrane serine protease 2 which induces the fusion of viral and cell membrane, which is why the virus affects men more severely than women.